Alcohol-responsive Action Myoclonus of the Leg in Prostate Cancer: A Novel Paraneoplastic Syndrome?. (22nd December 2015) - Termsarasab, Pichet; Frucht, Steven J.
Background: Paraneoplastic movement disorders in prostate cancer are rare, and to our knowledge paraneoplastic myoclonus has not previously been reported. Case Report: We report two men with adenocarcinoma of the prostate who developed isolated alcohol-responsive action myoclonus of one leg. Myoclonus was absent at rest but triggered by movement, standing, or walking. Evaluations excluded malignant invasion of the nervous system, and testing for commercial paraneoplastic antibodies in serum and cerebrospinal fluid were unrevealing. Both patients experienced significant improvement with alcohol, and sodium oxybate was used in one patient with good initial benefit. Discussion: Alcohol-responsive leg myoclonus might be a novel paraneoplastic syndrome associated with prostate cancer. The nature of the syndrome and the source of the myoclonus are currently unknown.